Oxygen transport and reactivity within a sandy seepage face in a mesotidal lagoon (Ria Formosa, Southwestern Iberia). (1st October 2015) - Ibánhez, J. Severino P.; Rocha, Carlos
Abstract: Sandy sediments are now recognized as sites of high carbon turnover enhanced by porewater flow. However, it is unclear how coupling between porewater advection and benthic metabolism might permit O2 ‐saturated areas and suboxic environments to coexist in close proximity. Field sampling campaigns, flow‐through reactor (FTR) experiments and diagenetic modeling were used to study benthic O2 dynamics in surface sediments of a permeable intertidal seepage face (Ria Formosa; Southwestern Iberia). Field results demonstrated that the pressure gradient imposed by tidal oscillation at the seepage face permits seawater infiltration at high tide, and hence resupplies the benthos in O2 and organic matter (OM). Significant aerobic respiration rates (12.1–26.8 nmol cm −3 "bulk sediment" (bs) h −1 ) were derived from vertical O2 gradients taken from the top 28 cm of the sediment during active seepage. FTR experiments showed a vertical zonation of respiration rates following benthic OM availability (from 8.63 ± 1.88 nmol cm −3 bs h −1 at 12–32 cm depth to 53.55 ± 7.93 nmol cm −3 bs h −1 at 0–2 cm depth). Advection enhances O2 consumption rates, but respiration is ultimately limited by OM availability at high seepage rates. Diagenetic modeling of O2 distribution in the porewater suggests that even within a well‐oxygenated beach aquifer, local respiration is sufficiently high to lower the porewater O2 concentration near the sediment surface during active seepage. Our results indicate that high seepage rates, OM and O2 loading promoted by tidally‐driven seawater infiltration control the O2 consumption at the sediment surface, thus favoring the occurrence of suboxic biogeochemical processes near the sediment surface.